Odor perception between heterosexual partners: Its association with depression, anxiety, and genetic variation in odorant receptor OR7D4 - Sookoian, Silvia Cristina (2011)
We performed a study on a sample of 856 individuals to answer whether the pleasantness/unpleasantness of the odor perception of their partners (rating of partner odor) is associated with depression and anxiety. To evaluate the influence of common genetic variation of the odorant receptor OR7D4 on the rating of partner odor, the variant rs8109935 was genotyped in the whole sample. The rating of partner odor was significantly associated with scores of anxiety and depression. Depression (OR: 0.75, 95%CI: 0.56–0.98, p = 0.039) and anxiety (Robust Coef ± SE: −13 ± 0.6, p = 0.044) were inversely associated with pleasantness rating of partner odor. Ordered probit regression analysis shows that the rating of partner odor was significantly associated with the rs8109935 genotypes (Coef ± robust SE: 0.19 ± 0.09, p = 0.028). These findings suggest that odor perception between heterosexual partners may have an impact on the development of depression and anxiety, and that it might be influenced by genetic variation in OR7D4.